Intravenous Immunoglobulin Treatment for Repeated IVF/ICSI Failure and Unexplained Infertility: A Systematic Review and a Meta‐Analysis. (December 2013) - Li, Jie; Chen, Yang; Liu, Chengjun; Hu, Yanling; Li, Liuming
<x xml:space="preserve">Abstract</x> Intravenous immunoglobulin (IVIG) has been introduced empirically into IVF/ICSI programs with the hopes of improving in vitro fertilization (IVF) success. However, the effects of IVIG have been inconsistent. We investigated the effects of IVIG on hard outcomes, including implantation rate, clinical pregnancy rate, live birth rate, miscarriage rate, and live birth rate per embryo transferred. The PubMed, EMBASE, and CNKI databases were searched up to June of 2013 and 10 studies were included. Case‐controlled studies comparing IVIG with placebo in IVF/ICSI women and/or unexplained infertility were included. Using fixed and random effects models, the pooled risk ratios (RR) with 95% confidence intervals (CIs) were calculated. The use of IVIG was significantly associated with a higher implantation rate and RR was 2.708 (95%CI: 1.302–5.629) compared with the placebo. The clinical pregnancy rate and the live birth rate were significantly increased in patients randomized to IVIG; RR was 1.475 (95%CI: 1.191–1.825) for the clinical pregnancy rate and RR was 1.616 (95%CI: 1.243–2.101) for the live birth rate. Moreover, the miscarriage rate was significantly less in patients randomized to IVIG (0.352, 95%CI: 0.168–0.738), but the live birthrate per embryo transferred was not (2.893; 95%CI: 0.810–10.331) less. Our results strongly support that IVIG is a useful treatment option for women undergoing repeated IVF failure.